Nim Chimpsky : the chimp who would be human - Hess, Elizabeth (New York : Bantam Books, 2008)
Tells the story of Nim Chimpsky, who in the 1970s was the subject of an experiment to find out whether a chimp could learn American sign language as well as other human-like traits.
Includes bibliographical references (p. [333]-356) and index.
Booklist.
Library Journal.
Pub Weekly.
Adult
Keywords: Chimpanzees -- Biography; Chimpanzees -- Psychology; Human-animal communication; Nim Chimpsky (Chimpanzee); Sign language; Chimpanzees -- Biography; Chimpanzees -- Psychology; Human-animal relationship; Nim Chimpsky (Chimpanzee); Sign language